Parallel profiling of cancer cells and proteins using a graphene oxide functionalized ac-EHD SERS immunoassay. Issue 39 (31st August 2018) - Reza, K. Kamil; Dey, Shuvashis; Wuethrich, Alain; Sina, Abu Ali Ibn; Korbie, Darren; Wang, Yuling; Trau, Matt
Abstract : Monitoring of circulating cancer biomarkers was enabled in a graphene oxide functionalised ac-EHD microfluidic device with SERS barcoding. Abstract : Circulating biomarkers have emerged as promising non-invasive, real-time surrogates for cancer diagnosis, prognosis and monitoring of the therapeutic response. Current bio-sensing techniques mostly involve detection of either circulating cells or proteins which are inadequate in unfolding complex pathologic transformations. Herein, we report parallel detection of cellular and molecular markers (protein) for cancer using a multiplex platform featuring (i) graphene oxide (GO) functionalization that increases the active surface area and more importantly reduces the functionalization steps for rapid detection, (ii) alternating-current electrohydrodynamic (ac-EHD) fluid flow that provides delicate micro-mixing to enhance target–sensor interactions thereby minimizing non-specific binding and (iii) surface enhanced Raman scattering (SERS) for multiplex detection. We find that our platform possesses high sensitivity for detecting both proteins and cells. More importantly, this platform not only detects the cancer cells but also can simultaneously monitor the heterogeneous expression of cell surface proteins which could be clinically useful to determine effective patient therapy. We demonstrate the specific and sensitive detection of breast cancer cells from a mixture of non-target cells and report the heterogeneous expression of human epidermal growth factor receptor 2 (HER2) proteins on the individual cancer cell surface. Concurrently, we detect as low as 100 fg mL −1 HER2 and Mucin 16 proteins spiked in blood serum.